PENGARUH LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA CV. JAYA KARYA PEKANBARU - Panca Dharma Pasaribu; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aimed to found factors which influenceemployee’s performance of CV. Jaya Karya Baru in pekanbaru. thosefactors were motivation and work environment. employees who have highwork motivation will give positive effect for organization, thereforeorganization purpose reached and could work well. Hypothesis examinationcarries out by spreads questionnaire about 20 sample of the employees atCV. Jaya Karya Pekanbaru, analysis that used was validity test, using likertscale on SPSS computer program version 16 by using double linearregression analysis. Work motivation variable consists seven factors whichresponded using the presentage of formula and would beanalyized by using Quantitve Description Technique.linear regression analysis methode on the Likert scale could concludewheter that work motivation variable have both positive and significantinfluence to employee’s work motivation. therefore, hypothesis which statedthat motivation have influence to employee’s work could be accepted.Simultaneously both work motivation and work environment havepositive and significant influence to employee’s performance and could beconcluded that both work motivation and work environment have significantinfluence to employee performance of CV. Jaya Karya PekanbaruKeywords: Employee’s performance, Work motivation and Workenvironment